BF3-catalysed methanolysis combined with fast atom bombardment tandem mass spectrometry as a new tool for the preparation and analysis of linear secocyclosporins - Havlícek, V; Jegorov, A; Sedmera, P; Ryska, M (Rapid communications in mass spectrometry, 1995)
BF3-catalysed methanolysis is presented for cyclic peptide cleavage using cyclosporins as model compounds. The reaction conditions for BF3-catalysed methanolysis of cyclosporins were optimized to favour the formation of linear undecapeptides. The resulting secocyclosporins were analysed by fast atom bombardment tandem mass spectrometry. Only one dominant and two side mechanisms of the ring opening are operating so that the complete sequence determination of all prepared oligopeptides was achieved.
Keywords: Molecular Sequence Data; katalýza; sekvence aminokyselin; Oligopeptides; Boranes; Methanol; oligopeptidy; Catalysis; Chromatography, High Pressure Liquid; spektrometrie hmotnostní - bombardování rychlými atomy; borany; vysokoúčinná kapalinová chromatografie; Amino Acid Sequence; Cyclosporins; cyklosporiny; methanol; molekulární sekvence - údaje; Hydrolysis; hydrolýza; Spectrometry, Mass, Fast Atom Bombardment